Item generation and content validation of the Hajjcrowd behavior (HBC) scale - Abdul Rahman, Shukran; Mohd Mahudin, Nor Diana; Mat Saad, Zarina; Sulong, Jasni; Ahmad Hatta, Zulkarnain; Mohd Hashim, Intan Hashimah; Abdul Ghani, Noraida (The Behavioral Science Research Institute (BSRI), Srinakharinwirot University, Bangkok, Thailand, 2017)
Our main objective is the development and initial validation of a new scale to measure crowd behavior of individuals who performed Hajj, i.e., a holy, religious pilgrimage to Mecca that Muslims take during the Islamic month of Dzul-Hijjah. A scale that measures this construct is important because an understanding of the nature, domains, and roles of crowd behavior could facilitate the effective management and safety of Hajj pilgrims or hujjaj. Using the logical or rational approach, the scale development process was conducted in three phases. First, the construct of Hajj crowd behavior was identified and conceptualized via a literature review (Phase I). Next, an initial pool of 93 items covering three domains of crowd behavior (i.e., behavioral, affective, and cognitive) was generated from a series of semi-structured interviews with 23 hujjaj (Phase II). The content validity of these items was then ascertained by the agreement of subject matter experts (n = 15), who indicated whether an item is essential in measuring a particular domain of the Hajj crowd behavior construct. This expert review revealed that the majority of items were essential, relevant, and clear (i.e., Content Validity Ratio: CVR > .49), which resulted in 52 items in the final item pool. This revised scale is now suitable to be used in the test try-out phase and has the potential to inform strategies and design of crowd management. Further work is needed to assess its reliability and validity as well as to reduce the number of the items.